Employing Question Writer Software Application (QW3) to create Quizzes in reading classes - Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2016)
This research entitled Employing Question Writer Software Application (QW3) to create Quizzes in reading classes. Evaluation is very important in teaching including teaching English as a foreign language and the quiz is one of the evaluations. As the rapid development of computer, technology and internet in society, the uses of this software can be very helpful for the lecturers mainly for those lecturers who want to apply the technology mainly software: Question writer (QW 3) that is really practical used in evaluation, quiz etc. This study is classified as an exploratory research in nature as it attempts to explore every bit of features at Question Writer QW3, a quiz maker application to see how much engineering can be used with respect to creating a particular quiz. This online quiz has received favorable responses from the students. The majority of them agreed that the online quiz is good to use as for practice. One of the reasons is that online quiz can be done elsewhere if the students happen to be able to do at the time of being assigned. Question Writer (QW) is a paid software application. It develops over time and on a regular basis. At the moment we are using QW3 and QW4.